A high-efficiency energy regenerative shock absorber using supercapacitors for renewable energy applications in range extended electric vehicle. (15th September 2016) - Zhang, Zutao; Zhang, Xingtian; Chen, Weiwu; Rasim, Yagubov; Salman, Waleed; Pan, Hongye; Yuan, Yanping; Wang, Chunbai
Graphical abstract: Highlights: A novel renewable energy application schemes was designed for range extension in EVs. A reliable mechanism was designed to change bidirectional vibration into unidirectional rotation. Supercapacitors were utilized to store the regenerative energy from the shock absorber. A high efficiency of 54.98% at most and 44.24% on average was obtained. The tested properties are suitable for replacing a conventional shock absorber. Abstract: The energy source of vehicles is changing rapidly and significantly in recent years with the increase in renewable energy technologies especially in the case of electric vehicles (EVs). A smart solution has emerged in which the wasted energy in a vehicle's shock absorber is converted to an alternative energy for the cars themselves, and this is called an energy regenerative shock absorber. Whereas existing regenerative shock absorbers mainly focus on the methods of energy harvesting, there is no such regenerative shock absorber for use in extended range EVs. In this paper, we present a novel high-efficiency energy regenerative shock absorber using supercapacitors that is applied to extend the battery endurance of an EV. A renewable energy application scheme using regenerative shock absorbers for range extended EVs is designed and proposed for the first time. This system collects the wasted suspension power from the moving vehicle by replacing the conventional shock absorbers as these energies are normally dissipated through friction and heat. The proposed system consists of four main components: the vibration of the suspension input module, transmission module, generator module and power storage module. The suspension vibration induced by the road roughness acts as the system excitation to the energy regenerative shock absorber. The vibration is then transmitted through the mechanical transmission module, which changes bidirectional vibration into unidirectional rotation based on gears and a rack to drive the generator module. The power storage module stores the regenerative energy of the shock absorber in the supercapacitor, which is applied to the EV to improve the cruising mileage. Higher efficiency up to 54.98% at most and 44.24% on average were achieved in the simulation and bench tests is proof that the energy regenerative shock absorber is beneficial and promising in generating energy used for renewable energy applications in extended range EVs.